Semecarpus impressicostatus - Hoo, P.K.; Tsen, S.; Damit, A.; Khoo, E.; Colin Ruzelion Maycock; Nilus, R.; Sabran, S.; Sugau, J.; Tanggaraju, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Semecarpus impressicostatus is restricted to the Telupid-Tongod area in eastern Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 12 km2 and 779 km2, respectively. It is known from three sites, two of which are within Totally Protected Areas (TPAs), however, forest fire remains a threat to these individuals as the sites are close to the border of the reserve. Land use change is a major threat to the subpopulation outside of the protected areas. Hence, it is assessed as Endangered. Semecarpus impressicostatus is endemic to Sabah, Malaysia. It is restricted to the Telupid-Tongod area in eastern Sabah.